Social entrepreneurship and business ethics : understanding the contribution and normative ambivalence of purpose-driven venturing - Zeyen, Anica; Beckmann, Markus (New York, NY : Routledge, 2019)
Social entrepreneurs are change makers that aim to solve society's unsolved problems. Not surprisingly, social entrepreneurship has thus created high expectations. To better understand the potential as well as the limitations of social entrepreneurship, however, a more nuanced approach is needed in two ways. First, social entrepreneurship is a multi-level phenomenon. It spans macro-level questions as well as meso-level questions and, finally, micro-level questions. If we really want to understand social entrepreneurship, we need to bring together all three levels of analysis and see how they are connected. Second, while social entrepreneurship can certainly produce socially desirable outcomes, we also need a critical perspective to capture potential undesirable effects that social entrepreneurship can cause, often unintendedly, in society, in markets, in organizations, and for individuals. To this end, an ethical perspective can help complement the positive analysis of social entrepreneurship with a discussion of the normative implications of its potential "dark side". Looking at social entrepreneurship from both a multi-level analysis and an ethical perspective, Social Entrepreneurship and Business Ethics takes the reader on a journey through the "bright side" as well as the potential "dark side" of social entrepreneurship for societies, organizations, and individuals. Highlighting both, this book not only seeks to provoke researchers and students to advance their understanding of social entrepreneurship. It also hopes to help practitioners to better realize the positive contributions of social entrepreneurship for society.
Chapter 1: Introduction -- Why Social Entrepreneurship and Business Ethics? Part I: Social Entrepreneurship and Business Ethics -- The Foundations Chapter 2: What is Social Entrepreneurship (not)? Chapter 3: Refining our Ethical Perspective on the Light and Shadows in Social Entrepreneurship: The Concept of Normative Ambivalence Part II: Society, Economy and Social entrepreneurship -- A Macro perspective Chapter 4: The Societal Function of Social Entrepreneurship -- Innovating in the Voids between Market and State Chapter 5: From Informal Economies to Welfare States: Social Entrepreneurship in Different Macro-level Contexts Part III: Social Entrepreneurship, Organizations, and Management -- A Meso Perspective Chapter 6: Social Mission and Hybrid Resources: Business Models in Social Entrepreneurship Chapter 7: Measuring Impact -- Blessing or Curse? Chapter 8: Scaling Social Ventures -- Growing the Limits or Limiting Growth? Part IV: Social Entrepreneurship and the Micro-Level Chapter 9: Social Mission, Agency, and Calling -- The Impact on Individuals within and around Social Ventures Chapter 10: Personality Traits, Abilities, and Intention: Can Mission-driven Venturing be Taught? Chapter 11: Narratives, Hagiographies, and Future Perspectives
OCLC-licensed vendor bibliographic record.
Keywords: Social entrepreneurship; Business ethics; BUSINESS & ECONOMICS -- Business Ethics